Concentration and other wage determinants - Ana Paula Martins (Economics and Econometrics Research Institute (EERI), 2018)
This research presents evidence on how the impact of industry concentration and unionism affect the Portuguese wage levels. The influence of employer association is also considered. We use sector information - two-digit level disaggregation of "Classificaç\~ao das Actividades Económicas" -, and control for other wage determinants, as usually done in earnings functions regressions. Dependent variables are logarithms of the mean sector wages considered for each case. Some statistical distribution indicators are also used to provide possible insights on the impact of skill composition and dispersion - eventually reflecting good assignment of people to jobs and/or tasks - on productivity and, thus, production.
Keywords: J31; J41; J42; J51; J56; J28; J24; J16; L10; L23; 330; Earnings Functions Determinants; Segmented Labor Markets; Wages and Job Risk; Male-Female Earnings/Wage Differentials; Market Structure and Wage Profiles; Firm Size and Wages (Efficiency Wages); Skill Mix and Wages